2024
DOI: 10.1101/2024.04.13.589363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOP/STIP1 is required for KSHV lytic replication

Elisa Kirigin,
Lorraine Matandirotya,
Jamie-Lee Ruck
et al.

Abstract: Kaposi sarcoma associated herpesvirus (KSHV) is a DNA virus that causes Kaposi sarcoma, a cancer of endothelial origin. KSHV uses the activity of host molecular chaperones like Hsp70 and Hsp90 for the folding of host and viral proteins required for productive infection. Hsp70 and Hsp90 chaperones form proteostasis networks with several regulatory proteins known as co-chaperones. Of these, Hsp90-Hsp70 organising protein (HOP) is an early-stage co-chaperone that regulates transfer of folding substrate proteins b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Hop is required for KSHV lytic replication. 37 Having established full-length Hop-HSP90 PPI inhibitory activity in conjunction with Hop engagement in cell lysates, we focused on assessing the impact that PPI inhibitory peptides 1 and 2 would have on the activation of KSHV lytic replication. To address possible cell-penetration limitations, we also generated Arg-8 CPP containing analogues of 1 (CPP-1, Figure 6C) and 2 (CPP-2), in addition to an MAAVD containing control (CPP-19).…”
Section: Kshv Lytic Replication Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hop is required for KSHV lytic replication. 37 Having established full-length Hop-HSP90 PPI inhibitory activity in conjunction with Hop engagement in cell lysates, we focused on assessing the impact that PPI inhibitory peptides 1 and 2 would have on the activation of KSHV lytic replication. To address possible cell-penetration limitations, we also generated Arg-8 CPP containing analogues of 1 (CPP-1, Figure 6C) and 2 (CPP-2), in addition to an MAAVD containing control (CPP-19).…”
Section: Kshv Lytic Replication Inhibitionmentioning
confidence: 99%
“…[34][35][36] Recently, we showed that Hop is required for KSHV lytic replication, with Hop depletion resulting in reduced transcription of KSHV lytic genes, reduced viral DNA load and reduced infectious virion production. 37 Rahimi and McAlpine have reported a suite of cyclic peptides whose binding to the HSP90-C-terminal region disrupted PPI formation with Hop, which in turn correlated with inhibition of HSP90-mediated luciferase refolding. 38,39 As an alternative strategy, we and others have sought strategies to disrupt this PPI through compounds which interact with Hop.…”
Section: Introductionmentioning
confidence: 99%